The Formation of Morality and Spirituality as the Primary Objectives within the Framework of Islamic Educational Philosophy - Wahidah Wahidah; Irfan Noor; Muhammad Iqbal (Integrated Education Journal, 2025)
This article aims to analyze the formation of morality and spirituality as the primary objectives within the framework of Islamic educational philosophy. The research focuses on how moral and spiritual values are positioned as the core of Islamic education and their relevance in addressing contemporary educational challenges. The research method employed is library research by examining various primary and secondary sources such as books, academic journals, and classical works of Islamic educational thinkers. The findings indicate that Islamic educational philosophy places moral and spiritual development as fundamental educational goals oriented toward forming the concept of insan kamil. Islamic education emphasizes not only cognitive development but also the integration of faith, knowledge, and righteous action. Therefore, Islamic education plays a strategic role in shaping individuals with strong moral character and deep spiritual awareness